Scientific Cosmopolitanism in 9th-Century Baghdad: Muslim, Jewish, and Christian Knowledge Exchange in Sociological Perspective - Umar, Zeindri Abu; Hidayat, Marwan; Qomarullah, Ahmad Basuki; Mutmainnah, Rizky (Al-Qarawiyyin: Jurnal Ilmu Ushuluddin, 2025)
The 9th century was a pivotal phase in Islamic intellectual history, when Baghdad, under the Abbasid dynasty, emerged as a cosmopolitan center of knowledge. However, studies on interfaith interactions in the social construction of knowledge have rarely been discussed sociologically, particularly regarding the mechanisms of collaboration and the driving forces behind them. This study aims to analyze the exchange of knowledge between Muslim, Jewish, and Christian communities through social relations, institutions, and scientific networks, and to examine how these interactions have shaped cosmopolitan structures for the development of knowledge. This study employs a qualitative method with a historical-sociological approach, drawing on both primary and secondary literature. This study examines the role of Bayt al-Ḥikmah, the patronage of the caliphs, and the contributions of translators and scholars across religions through their works, institutions, and intellectual networks. The results show that Christian translators played a strategic role in transmitting Greek works through philological phases and conceptual adaptations. At the same time, Muslim scholars developed a methodological synthesis that connected rationalism and theology in the fields of philosophy, medicine, and mathematics. The Jewish community also made significant contributions to the development of philology and philosophy, which later had a profound influence on the Andalusian intellectual tradition. These findings confirm that Baghdad’s scientific cosmopolitanism was not simply the result of knowledge transfer, but rather a social construct shaped by epistemic tolerance, institutional cooperation, and cultural openness. In conclusion, interfaith interactions during this period gave rise to a knowledge ecosystem model that was not only productive and collaborative but also accelerated methodological integration and the expansion of the intellectual horizons of the Islamic world.